John T. Sidel. 2021. Republicanism, Communism, Islam: Cosmopolitan Origins of Revolution in Southeast Asia. Ithaca: Cornell University Press. 324 pp. ISBN 9781501755613 - Bayona, Jorge (El Colegio de México, 2023)
John T. Sidel. 2021. Republicanism, Communism, Islam: Cosmopolitan Origins of Revolution in Southeast Asia. Ithaca: Cornell University Press. 324 pp. ISBN 9781501755613